Analisis Kontestasi Kelembagaan DPD dan Upaya Mengefektifkan Keberadaannya - Masnur Marzuki (Jurnal Hukum IUS QUIA IUSTUM, 2008)
In considering the principle of check and balances in legislature matter, the grand theme should be proposed in this context is how to guarantee checks and balances within the legislative branch and that principle are implemented properly and reliably. Nonetheless, in Indonesian constitutional system after the Reformation era when the House of Regional Representative (DPD) was established, the achivement of check and balances is still far from its fundamental aim. As a result, the “new” Constitution is challenged to observe an ideal parliament system where checks and balances within the legislative branch can be achieved and the existence of such fundamental institution could effectively bridge local aspiration to national policy.